Studi Eksperimental Sistem Pengarah Aliran Pada Turbin Hidrokinetik Archimedes Spiral - Adri Pratama; Dwi Anung Nindito; Raden Haryo Saputra (Universitas Negeri Gorontalo, 2021)
Changes in flow direction due to drag and lift forces that hit the Archimedes Spiral hydrokinetic turbine is a problem that could affect turbine performance, hence, it is important to add a flow steering system. This study aims to determine the effect of adding a flow guide system in the form of a truncated cone and tail guide on the performance of the Archimedes Spiral turbine. The method used is experimental tests on turbine performance using several variations of flow velocity in open channels. The results of the study show that the Archimedes Spiral turbine with a flow guide system produces a Cp value of 0.19–0.22 and a TSR value of 1.76–1.85. The torque value obtained is in the range of 0.013–0.017 Nm within the range of 28.64–33.60 RPM. The addition of a truncated cone was able to increase the flow capture force. The addition of a guide tail could forward the vortex flow lengthwise to the downstream of the turbine. The forwarded vortex flow inhibits the rotation of the turbine blades and causes the compressive force on the turbine to increase. The increased compression force on the blade caused the torque value to increase. In the Archimedes Spiral turbine with the addition of a flow steering system, the increased torque caused the concept drag force to be higher than the concept of lift force. The addition of a truncated cone and guide tail increased the performance of the Archimedes Spiral turbine.